Fecal and Salivary Cortisol Concentrations in Woolly (Lagothrix ssp.) and Spider Monkeys (Ateles spp.) - Ange-van Heugten, Kimberly D.; van Heugten, Eric; Timmer, Saskia; Bosch, Guido; Elias, Abahor; Whisnant, Scott; Swarts, Hans J. M.; Ferket, Peter; Verstegen, Martin W. A. (International Journal of Zoology, 2009)
Detrimental physiological effects due to stressors can contribute to the low captive success of primates. The objective of this research was to investigate the potential impact of diet composition on cortisol concentrations in feces and saliva in woolly (n=27) and spider monkeys (n=61). The research was conducted in three studies: the first investigated spider monkeys in the United States, the second investigated spider monkeys within Europe, and the third investigated woolly monkeys within Europe. Fecal cortisol in spider monkeys in US zoos varied (P=.07) from 30 to 66 ng/g. The zoo with the highest fecal cortisol also had the highest salivary cortisol (P≤.05). For European zoos, fecal cortisol differed between zoos for both spider and woolly monkeys (P≤.05). Spider monkeys had higher fecal cortisol than woolly monkeys (P≤.05). Zoos with the highest dietary carbohydrates, sugars, glucose, and fruit had the highest cortisol. Cortisol was highest for zoos that did not meet crude protein requirements and fed the lowest percentage of complete feeds and crude fiber. Differences among zoos in housing and diets may increase animal stress. The lifespan and reproductive success of captive primates could improve if stressors are reduced and dietary nutrients optimized.